2016
DOI: 10.1053/j.gastro.2016.02.071
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between CEL–HYB Hybrid Allele and Chronic Pancreatitis in Asian Populations

Abstract: A hybrid allele between the carboxyl ester lipase gene (CEL) and its pseudogene, CELP (called CEL-HYB), generated by nonallelic homologous recombination between CEL intron 10 and CELP intron 10', was found to increase susceptibility to chronic pancreatitis in a case-control study of patients of European ancestry. We attempted to replicate this finding in 3 independent cohorts from China, Japan, and India, but failed to detect the CEL-HYB allele in any of these populations. The CEL-HYB allele might therefore be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 17 publications
1
55
0
1
Order By: Relevance
“…For conventional reverse‐transcription polymerase chain reaction (RT‐PCR) analyses, 1 µg wild‐type or variant plasmid, mixed with 2 µl jetPEI DNA transfection reagent (Polyplus‐transfection), was used for transfection per well. For real‐time quantitative RT‐PCR analyses, 500 ng wild‐type or variant plasmid was mixed with 500 ng pGL3‐GP2 minigene for transfection (Boulling, Chen, Callebaut, & Férec, ; Zou, Boulling, Masamune, et al, ; Zou et al, ). Forty‐eight hours after transfection, total RNA was extracted using the RNeasy Mini Kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…For conventional reverse‐transcription polymerase chain reaction (RT‐PCR) analyses, 1 µg wild‐type or variant plasmid, mixed with 2 µl jetPEI DNA transfection reagent (Polyplus‐transfection), was used for transfection per well. For real‐time quantitative RT‐PCR analyses, 500 ng wild‐type or variant plasmid was mixed with 500 ng pGL3‐GP2 minigene for transfection (Boulling, Chen, Callebaut, & Férec, ; Zou, Boulling, Masamune, et al, ; Zou et al, ). Forty‐eight hours after transfection, total RNA was extracted using the RNeasy Mini Kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…All 1,112 Chinese ICP patients (776 males and 336 females) were of Han origin. A clinical diagnosis of ICP was made as previously described (Zou et al., ) (see also Supp. Methods).…”
Section: Rare Functionally Deficient Cpa1 Variants In Chronic Pancreamentioning
confidence: 99%
“…The c.194G>A variant was introduced into the wild-type full-length SPINK1 expression vector by directed mutagenesis; reverse transcription-PCR (RT-PCR) analyses of mRNAs from subsequently transfected HEK293T cells revealed a single transcript of similar size to the wild type (figure 1A); sequencing of the RT-PCR products revealed that the variant transcript was correctly spliced as per the wild type. We then performed quantitative RT-PCR analyses of the wild type and c.194G>A variant mRNA expressions as previously described,7 except that the primers used for amplifying the full-length target gene transcripts were changed to the primer pair Q1 as described in ref. 6.…”
mentioning
confidence: 99%